Thermal simulation of heterogeneous structural components in microelectronic devices - Gavrysh, V.I.; Fedasyuk, D.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
The steady state nonlinear problem of thermal conduction for isotropic strip
with foreign rectangular inclusion that heats as an internal thermal source with heat
dissipation has been considered. The methodology to solve this problem and its
application for the specific dependence of the thermal-conductivity coefficients on
temperature has been offered.